The first-nucleotide binding domain of the cystic-fibrosis transmembrane conductance regulator is important for inhibition of the epithelial Na(+) channel - Schreiber, Rainer (The National Academy of Sciences, 1999)
The cystic-fibrosis transmembrane conductance regulator (CFTR) functions as a cAMP-regulated Cl(−) channel and as a regulator of other membrane conductances. cAMP-dependent activation of CFTR inhibits epithelial Na(+) channels (ENaC). The specificity of interaction between CFTR and ENaC was examined by coexpression of ENaC and ATP-binding cassette (ABC) proteins other than CFTR. In addition, we identified domains within CFTR that are of particular importance for the inhibition of ENaC. To that end, two-electrode voltage-clamp experiments were performed on Xenopus oocytes coexpressing ENaC together with CFTR, the multidrug resistance protein MDR1, the sulfonyl urea receptor SUR1, or the cadmium permease YCF1. Except for CFTR, none of the other ABC proteins were able to inhibit ENaC. Several truncated versions of CFTR were examined for their inhibitory effects on ENaC. In fact, it is shown that C-terminal truncated CFTR is able to inhibit ENaC on activation by intracellular cAMP. Moreover, the data also show that an intact first-nucleotide binding domain (NBF-1) is important for inhibition of ENaC. We conclude that NBF-1 of CFTR contains a CFTR-specific regulatory site that down-regulates ENaC. It is speculated that this regulatory site also is needed for CFTR-mediated interactions with other membrane proteins and that it is not present in NBF-1 of other ABC proteins.